2009
DOI: 10.1002/pro.175
|View full text |Cite
|
Sign up to set email alerts
|

Conformational changes in redox pairs of protein structures

Abstract: Disulfides are conventionally viewed as structurally stabilizing elements in proteins but emerging evidence suggests two disulfide subproteomes exist. One group mediates the well known role of structural stabilization. A second redox-active group are best known for their catalytic functions but are increasingly being recognized for their roles in regulation of protein function. Redox-active disulfides are, by their very nature, more susceptible to reduction than structural disulfides; and conversely, the Cys p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 125 publications
(126 reference statements)
0
46
0
Order By: Relevance
“…The importance of reversible disulfide bond formation as a central feature of redox regulation is increasingly recognized (15,(19)(20)(21)(22)(23)(24). We have verified the predicted enhancement in Pol β binding affinity using a fluorescence binding assay and a stabilized analog of oxidized XRCC1-NTD.…”
Section: Discussionmentioning
confidence: 59%
“…The importance of reversible disulfide bond formation as a central feature of redox regulation is increasingly recognized (15,(19)(20)(21)(22)(23)(24). We have verified the predicted enhancement in Pol β binding affinity using a fluorescence binding assay and a stabilized analog of oxidized XRCC1-NTD.…”
Section: Discussionmentioning
confidence: 59%
“…However, recent studies reveal that number of bacterial proteins have been identified that seems to be regulated by change in the redox of the cytosol enabling them to survive in ROS environment (Takahashi, 2012;van der Heijden et al, 2014;Vatansever et al, 2013;Wang et al, 2012). Reports are available where proteins containing catalytic zinc sites are redox regulated and exist in both oxidized and reduced forms (Castro et al, 2008;Fan et al, 2009;Fig. 8 (continued) Lowther et al, 2000;Wouters et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Proteins that form disulfide bonds following expulsion of metals such as Zn 2+ are shown to be redox regulated (Fan et al, 2009;Wouters et al, 2010). Earlier reports indicate that the Zn 2+ dependent enzymes are prone to oxidative inactivation followed by loss of Zn 2+ (Castro et al, 2008;Evans et al, 2002;Fan et al, 2009;Janda et al, 2004;Miller et al, 2005) and reductive reactivation by reducing agents in the presence of zinc chloride (ZnCl 2 ) (Castro et al, 2008;Evans et al, 2002;Lowther et al, 2000;Miller et al, 2005;Qiu et al, 1994).…”
Section: Hgchii Can Exist In Active or Inactive Form Depending On Itsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, these latter redox-active disulfides have high redox potentials, ranging from -120 to -270 mV, in contrast to structural disulfides, whose redox potential can be as low as -470 mV [65]. This property makes the former bonds more prone to be reduced, and also makes the Cys pairs that form them more susceptible to oxidation [65]. In this way, these active disulfide bridges act as highly sensitive redox switches for the regulation of protein function, which might be achievable by altering protein conformation.…”
Section: Force-induced Disulfide Bond Reductionmentioning
confidence: 99%